Kuasa Kata Di Media Sosial dalam Paradigma Pemberitaan Kompas dan Tempo - Djony Herfan; Nurul Intan Pratiwi; Ade Haryani (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
This research focuses on the issue of the power of words in media. The problem is the intertwined reporting between social media and mainstream media. The purpose of the study is to achieve the power of words in the accuracy of news. Words are intertwined in the news for language editors both in the Kompas and Tempo media. In general, the use of words on social media uses mixed language. The confusion of the use of words is reflected in the confusion of meaning. The meaning of words through social media is also intertwined with the use of foreign language words (English), alay, slang, and